Las humanidades, siempre - Quiroz Ávila, Rubén (2023)
Since its birth as a university in 1551, the humanities have been an intrinsic part of the intellectual life of the University of San Marcos. That the humanistic is a foundational part of our educational institution is a clear sign of its absolute importance in its history. Therefore, over the centuries that have passed, the diverse approaches that have been proposed by the humanistic disciplines account for the conceptual richness and the constant discursive plots that they debate. Those who dedicate themselves to the humanities, in all their variants, suggest, without appealing to absolute truths, diverse interpretations that are constantly put up for discussion and, without hesitation, sharply questioned.